Implementasi Program Bantuan Sosial di Lingkungan Pemasyarakatan: Studi Kasus UPT Pemasyarakatan Kanwil Ditjenpas Jawa Timur - Faiz Alfianshah, Ardi; Sebastian Iskandar, Irvan (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study aims to analyze the implementation of social assistance programs at the Technical Implementation Unit (UPT) of Corrections within the East Java Regional Office of the Directorate General of Corrections using the Van Meter and Van Horn policy implementation model. This study uses a qualitative approach with data collection through interviews with structural officials and implementing officers at Correctional Technical Implementation Units, documentation studies, and policy reviews. The analysis focuses on six implementation variables, namely policy standards and objectives, resources, characteristics of the implementing organization, inter-organizational communication, implementer disposition, and social, economic, and political conditions. The results show that the implementation of social assistance programs has been active in most UPTs, mainly through the utilization of local potential and integration with inmate rehabilitation programs. However, implementation still faces obstacles in the form of the absence of standard operating procedures, budget constraints, variations in the determination of target recipients, and weak vertical communication between the UPT and the regional office level. These findings indicate that the implementation of social assistance programs in correctional facilities tends to be a local initiative and has not been institutionalized in policy. Therefore, more operational derivative policies, strengthened coordination, and integration of recipient data are needed so that social assistance programs can be implemented consistently, sustainably, and on target.